Improving the inclusion of an under-served group in trials: development and implementation of the INCLUDE Impaired Capacity to Consent Framework - Shepherd, Victoria; Joyce, Katherine; Lewis, Amanda; Flynn, Samantha; Clout, Madeleine; Nocivelli, Brittany; Segrott, Jeremy; Treweek, Shaun (Current controlled trials in cardiovascular medicine, 2024)
Background For the potential benefits of trials to reach all that they should, trials must be designed to ensure that those taking part reflect the population who will receive the intervention. However, adults with impaired capacity to consent are frequently excluded from trials — partly because researchers are unfamiliar with the legal and ethical frameworks and lack the necessary methodological expertise. Researchers identified a need for guidance on designing more inclusive trials. Building on the NIHR INCLUDE initiative, we developed the INCLUDE Impaired Capacity to Consent Framework to help researchers design inclusive trials. Methods The framework was developed over five phases: (1) establishing the scope and content of the framework and adapting the INCLUDE Ethnicity Framework for this population; (2) scoping the relevance of the framework to different populations and piloting in a range of trials; (3) consulting people living with impairing conditions and carers to explore their views about the framework and identify missing content areas; (4) refining the framework; and (5) the development of an implementation toolkit of resources to support researchers using the framework. Results The framework has two parts: a set of four key questions to help researchers identify who should be included in their trial, and a series of worksheets covering intervention design, recruitment and consent processes, data collection and analysis, and public involvement and dissemination. It is supported by a summary of the ethical and legal frameworks and a website of resources on capacity and consent. Implementation resources include infographics and animations, a library of completed frameworks, and facilitated workshops for researchers. The framework and toolkit were launched at a webinar (November 2022), with polling demonstrating an increase in attendees’ awareness about research involving adults lacking capacity. A post-webinar survey found that stakeholders viewed the framework and toolkit as valuable tools to facilitate greater inclusion of this under-served population in trials. The framework is available online: https://www.capacityconsentresearch.com/include-impaired-capacity-to-consent-framework.html . Conclusions The INCLUDE Impaired Capacity to Consent Framework and implementation toolkit can support researchers to design more inclusive trials and other types of research studies. Further engagement, including with funders who are key to ensuring uptake, and evaluation is needed.